Liquid-Liquid Extraction Study of Sodium and Potassium Ions by a Series of Non Cyclic Ionophores Composed of Furan Units - L. Lokwani (Journal of Sciences, Islamic Republic of Iran)
A new series of noncyclic ionophores containing two to four furan units (Ia to IIIb) i.e. 1,1-difurylethane (Ia), 2,5-bis(methylfurfuryl)furan (IIa) and 1,1’ ethyledenebis[5-(methylfurfuryl)furan] (IIIa), 2,2-difurylpropane (Ib), 2,5-bis (dimethylfurfuryl)furan(IIb), 2,2’-isopropylidenebis[5-(dimethylfurfuryl)furan] (IIIb) have been synthesized by the condensation of furan with acetaldehyde and acetone in ethanol separately in the presence of concentrated hydrochloric acid. These ionophores were used for the extraction of alkali metal ions from aqueous to organic phase in chloroform membrane using picrate, dinitrophenolate and orthonitrophenolate salts. All ionophores of series (a) and (b) extract K+ selectively over Na+ and ligands IIa and IIb show the best extraction efficiency for K+ among these series. Among anions, orthonitrophenolate is found to be the best in comparison to dinitrophenolate and picrate during extraction. Thus, we can control the extraction of cations by altering anion.